2015
DOI: 10.1021/acs.joc.5b00407
|View full text |Cite
|
Sign up to set email alerts
|

The Biginelli Reaction Is a Urea-Catalyzed Organocatalytic Multicomponent Reaction

Abstract: The recently developed artificial force induced reaction (AFIR) method was applied to search systematically all possible multicomponent pathways for the Biginelli reaction mechanism. The most favorable pathway starts with the condensation of the urea and benzaldehyde, followed by the addition of ethyl acetoacetate. Remarkably, a second urea molecule catalyzes nearly every step of the reaction. Thus, the Biginelli reaction is a urea-catalyzed multicomponent reaction. The reaction mechanism was found to be ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 84 publications
0
48
0
Order By: Relevance
“…The mechanism of the Biginelli reaction, using acidic Brönsted or Lewis catalysts, was discussed by several authors [13,21,22]. Kappe [23,24], re-examining this question concluded that the first step in this mechanism:" involves the acid-catalysed formation of an N-acyliminium ion precursor from and aldehyde and urea component".…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the Biginelli reaction, using acidic Brönsted or Lewis catalysts, was discussed by several authors [13,21,22]. Kappe [23,24], re-examining this question concluded that the first step in this mechanism:" involves the acid-catalysed formation of an N-acyliminium ion precursor from and aldehyde and urea component".…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐based heterogeneous catalysts such as polymers supported metal nanoparticles, ionic liquids, zeolites, acidic surfactants, ion exchange resins, Lewis acids, metal nanoparticles, urea, silica supported sulfonated graphene oxide, etc. are reported . Rate enhancement using ultrasound as well as microwaves is also been reported.…”
Section: Introductionmentioning
confidence: 90%
“…Compound 5 was synthesized by the four components Biginelli-like cyclocondensation reaction of tert -butyl β-ketoester (1.0 mmol) ( 1 ), propargyl alcohol (1.2 mmol) ( 2 ), substituted aryl aldehyde (1.0 mmol) ( 3 ), and urea (1.2 mmol) ( 4 ) by a reflux method 39. The entire reaction mixture was allowed to stir for 3 hours at room temperature along with a catalytic amount of Cu(OAc) 2 (0.1 mmol) and sodium ascorbate (0.2 mmol) in a 1:2 ratio of acetone and water (2 mL) as a solvent till the reaction was complete.…”
Section: Methodsmentioning
confidence: 99%